Age-dependent changes of stress and strain in the human heart valve and their relation with collagen remodeling. (1st January 2016) - Oomen, P.J.A.; Loerakker, S.; van Geemen, D.; Neggers, J.; Goumans, M.-J.T.H.; van den Bogaerdt, A.J.; Bogers, A.J.J.C.; Bouten, C.V.C.; Baaijens, F.P.T.
Graphical abstract: Abstract: In order to create tissue-engineered heart valves with long-term functionality, it is essential to fully understand collagen remodeling during neo-tissue formation. Collagen remodeling is thought to maintain mechanical tissue homeostasis. Yet, the driving factor of collagen remodeling remains unidentified. In this study, we determined the collagen architecture and the geometric and mechanical properties of human native semilunar heart valves of fetal to adult age using confocal microscopy, micro-indentation and inverse finite element analysis. The outcomes were used to predict age-dependent changes in stress and stretch in the heart valves via finite element modeling. The results indicated that the circumferential stresses are different between the aortic and pulmonary valve, and, moreover, that the stress increases considerably over time in the aortic valve. Strikingly, relatively small differences were found in stretch with time and between the aortic and pulmonary valve, particularly in the circumferential direction, which is the main determinant of the collagen fiber stretch. Therefore, we suggest that collagen remodeling in the human heart valve maintains a stretch-driven homeostasis. Next to these novel insights, the unique human data set created in this study provides valuable input for the development of numerical models of collagen remodeling and optimization of tissue engineering. Statement of significance: Annually, over 280, 000 heart valve replacements are performed worldwide. Tissue engineering has the potential to provide valvular disease patients with living valve substitutes that can last a lifetime. Valve functionality is mainly determined by the collagen architecture. Hence, understanding collagen remodeling is crucial for creating tissue-engineered valves with long-term functionality. In this study, we determined the structural and material properties of human native heart valves of fetal to adult age to gain insight into the mechanical stimuli responsible for collagen remodeling. The age-dependent evolutionary changes in mechanical state of the native valve suggest that collagen remodeling in heart valves is a stretch-driven process.